Compact UWB Antenna with Triple Band-Notches Using C-Shaped and S-Shaped Structures - Ma, Zhenyang; Dong, Feifei; Han, Zheng; Han, Shaocheng; Xue, Qiannan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A semi-ellipse planar monopole UWB antenna with triple band-notched characteristics is presented. The proposed antenna with three band notches can operate in 3-13.9 GHz which covers the UWB (3.1-10.6 GHz) frequency range. Triple band-notched characteristics is achieved by etching a C-shaped slot on main radiator and adding two novel modified S-shaped cells on either side of microstrip line. The antenna is designed to reject the WiMAX (3.3-3.7 GHz), WLAN (5.15-5.825 GHz), and the downlink of X-band satellite communication systems (7.25-7.75 GHz). The proposed antenna is designed on FR4 substrate of size 20×26×1 mm3. Details of the antenna design and analysis are presented in this paper.